OBSERVATIONS ON THE AQUATIC FAUNA OF THE CAVES OF VALLES SAN LUIS POTOSI MEXICO - OSORIO TAFALL, B F (Livestock Research, Palo Alto, CD MEXICO, DF, MEX, 1947)
This is a useful bibliog on Homo neanderthalensis, listing the major articles which have appeared up to 1940
REV SOC MEX HIST NAT
Keywords: OBSERVATIONS, AQUATIC FAUNA, CAVES OF VALLES, SAN LUIS POTOSI MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA)